Probiotics in Sports: Modulating the Microbiome for Performance and Health - Moliszewska, Katarzyna; Kukiełka, Paweł; Kośka, Joanna; Łocik, Gabriela; Mazurek, Julia; Załęcka, Julia; Nowik, Alicja; Dywan, Kacper; Musiorska, Martyna; Błaszkiewicz, Michał (Quality in Sport, 2025)
Background The human gut microbiome—a dynamic ecosystem of bacteria, viruses, fungi, and archaea—is integral to digestion, immune modulation, metabolism, and systemic health. Its composition is shaped by perinatal factors, genetics, environment, diet, physical activity, and probiotic interventions. Modulating the microbiome through lifestyle and nutritional strategies offers potential for disease prevention and enhanced athletic performance. Aim This review synthesizes current evidence on factors influencing gut microbiota composition across the lifespan, the systemic impacts of dysbiosis, and the roles of diet, physical activity, and probiotics—particularly in athletic populations—in fostering a health-promoting microbiome. Material and Methods A narrative review was conducted using peer-reviewed studies, meta-analyses, and clinical trials sourced from PubMed, Scopus, and Web of Science. Topics included microbiome development, lifestyle and dietary influences, exercise-related microbiome adaptations, and probiotic applications. Results Perinatal factors such as delivery mode, breastfeeding, and antibiotics shape early microbiota with long-term health effects. Diet is a primary modulator: fiber- and polyphenol-rich diets enhance microbial diversity, whereas high-protein, low-fiber diets may impair gut health in athletes. Physical activity modifies microbiota structure and function; regular exercise promotes beneficial SCFA-producing taxa, strengthens gut barrier integrity, and supports immune and neurocognitive health. Probiotic supplementation improves gastrointestinal and dermatological conditions, modulates inflammation, and enhances athletic recovery and resilience. Conclusions The gut microbiome is a key determinant of systemic health. Targeted diet, structured physical activity, and personalized probiotic use can optimize microbiota function. In athletes, integrating microbiome profiling with individualized nutrition may enhance performance and recovery.